Error Analysis on The Use of Possessive Pronouns of The Tenth-Grade Students at SMA Negeri 3 Tangerang Selatan - Alfariha, Fika; Hadi, Muhamad Sofian (Jurnal Studi Guru dan Pembelajaran, 2024)
Since there are so many different kinds of pronouns in English, students often make an error, particularly when using possessive pronouns. Therefore, this study, which involved 36 students in class 10th at SMA Negeri 3 Tangerang Selatan, was conducted to identify the different kinds of errors made by students when using possessive pronouns. Knowing these errors can help find solutions to overcome them. The aim of this research is to: 1) To find out the types of students' errors in using possessive pronouns in sentences. 2) Explain the solution to help students understand how to use possessive pronouns in sentences. The method used in this research is a qualitative method. Data collection techniques in this research are interviews and documentation. Data analysis uses Miles and Huberman theory, by means of data reduction, data presentation and verification. The results of this research are: 1) the mistakes made by students in using possessive pronouns in sentences were in the pronoun "his" as many as 23 students answered incorrectly, in the pronoun "my" as many as 18 students were incorrect, in the pronoun "her" as many as 19 students were incorrect, "our and it" 5 students got it wrong, and 2 students got the pronoun "mine" wrong. 2) The solution to overcome errors in using possessive pronouns is mind mapping, re-explanation, and memorizing.